ANALISIS MUTU BIODIESEL DAN RANCANGAN PERBAIKAN DI PT X DENGAN PENETAPAN KADAR TRIGLISERIDA SEBAGAI STANDAR - Masdania Zurairah; Ansari Ansari; Joko Suprianto (Program Studi Kimia - Universitas Sari Mutiara Indonesia, 2021)
Research has been carried out at PT X in managing palm oil into biodiesel products. To get biodiesel from palm oil, it undergoes processes such as purification, transesterification and then methyl ester or biodiesel is produced. The biodiesel produced is a reaction between triglycerides (vegetable oil) and the chemical compound methanol with a catalyst. The company sets the standard for biodiesel to have a maximum triglyceride content of 0.2%. The production data turned out to show triglyceride levels above 0.2% with a very large number of outspec products so this indicates a problematic production system. Loss of quality or Quality Loss Function, this is due to damage in the manufacturing process stage, which will suffer losses, in the form of material, time, energy. At this stage the methanol used per hour is 4783 kg/hour and the catalyst is 773 kg/hour. This data is obtained from the total use of vegetable oil materials in 1 hour which is 46 tons/hour.